On a new species of the rare syllid genus Exogonoides (Annelida, Phyllodocida, Syllidae) - Fukuda, Marcelo Veronesi; Martín, Guillermo San; Carrerette, Orlemir; Paresque, Karla (Zootaxa, 2016)
The genus Exogonoides Day, 1963, was described probably based on a single specimen, broken into two pieces (Aguado & San Martín 2008) and no other specimens of the type species, E. antennata Day, 1963, were ever found, which characterizes this species and, until now, the very genus Exogonoides, as ‘singletons’ (Lim et al. 2012). Although described as a member of the Syllidae Grube, 1850, the positioning of the genus in the family was recently questioned (Aguado & San Martín 2008), since the pharynx of the holotype was dissected for the original description and not preserved with the specimen, resulting that the presence of the proventricle, considered the main synapomorphy of the family, could not be confirmed.